내경정맥도관 삽입술후 발생한 수흉증 - 김영호; Young Ho Kim; 조성두; Seong Doo Cho; 송남원; Nam Weon Song; 구철회; Choul Hae Koo; 김학렬; Hak Lyul Kim (Korean journal of anesthesiology, 1991)
Cannulation of the internaliugular vein was first described by English et al in l969; since then, it has steadily increased in popularity to its present position as one of the methods of choise for CVP monitorimg. But this method of CVP monitoring has some potential compolication such as infection, thrombophlebitis, pneumothorax, hydrothorax, hematoma, air embolism, catheter shearing, nerve injuries & pericardial tamponade, etc. We experienced a case of hydrothorax following internal jugular vein catheterization.